ANALISIS PERENCANAAN STRUKTUR GEDUNG ASRAMA PUTRA PESANTREN MUHAMMADIYAH LIMA KAUM KABUPATEN TANAH DATAR - Masril, Masril; Zuendra, Aulia (Ensiklopedia of Journal, 2024)
Dormitory Pesantren Muhammadiyah Lima Kaum is planned as a supporting building for students to stay and also to improve the discipline of the students and improve learning outcomes. This planning aims to determine the dimensions and reinforcement of the building structure, to calculate the loading that works on the structure to be planned. As for the benefits of this planning, knowing how to analyze the bui lding structure based on earthquake loads, adding insight in the field of structural planning, especially in  the planning of multi-storey building structures, and as a reference for the construction of this dormitory. This building has a floor area of 1. 074 m2 consisting of 4 floors, for the material the author uses steel quality fy =420 Mpa and concrete quality f'c = 24.9 Mpa obtained dimensions of the main beam B1 45 cm x 30 cm reinforcement top 5D - 16 and reinforcement bottom 3D - 16, main beam B2 40 cm x 25 cm reinforcement top4D - 16 and reinforcement bottom 2D - 16, and child beam B3 40 cm x 25 cm top reinforcement 5D-16 and bottom  reinforcement  3D-16,  while  for  column  dimensions,  column  K1  60  cm  x  60  cm  with  24D-19 reinforcement and column K2 45 cm x 45 cm with 12D-19 reinforcement are obtained, and for plates 15 cm thick with 10Ø-150 mm reinforcement.Keywords: Dormitory, Boarding School, Structure, Building, Method